Using soil amendments and mycorrhiza to improve chemical properties of degraded calcareous soil and yield of sorghum in dryland - Matheus, Rupa; Kantur, Donatus; Levis, Leta Rafael (Brawijaya University, 2024)
Optimized use of calcareous soil in dryland areas needs to begin with rehabilitation efforts using soil amendments, including organic fertilizer and biochar. This study sought to determine whether kinds of soil amendments and mycorrhizal biofertilizers may enhance the chemical quality of calcareous soils and increase the yield of sorghum on dry land. The study was conducted at the experimental garden of the Agricultural Extension Center located in Oelnasi Village from April to August of 2023. Two criteria included in the study were the kind of soil amendment and mycorrhizal biological fertilizer, both of which were arranged in a randomized block design. The parameters observed were soil chemical properties, plant N and P nutrient uptake, and sorghum yield. The research results showed that the application of three types of soil amendments (P1 = cow dung, P2 = rice straw compost, and P3 = corncob biochar) improved the chemical quality of calcareous soil. This application of corncob biochar could significantly reduce soil pH from 7.85 (slightly alkaline) to 7.19 (neutral) and increase soil organic C to 2.55% C, followed by treatment with cow dung and rice straw compost. Other soil chemical properties, i.e., N, P, K, and soil CEC, also improved, which differed from the control treatment. The mycorrhizal biofertilizer provided could also improve the chemical properties of calcareous soil. Providing mycorrhizal biofertilizer could increase the N and P nutrient uptake of sorghum plants by 3.79% dry weight-1 and 2.18% dry weight-1, respectively, as well as increased sorghum yields, respectively by 4.04 t ha-1, 3.97 t ha-1 and 3.87 t ha-1 dry beans, higher than the control which only achieved 2.32 t ha-1 dry beans.